Changes in the Seasonally Frozen Ground Over the Eastern Qinghai-Tibet Plateau in the Past 60 Years - Wang, Chenghai; Zhao, Wen; Cui, Yang (Frontiers in Earth Science, 2020)
The Qinghai-Tibet Plateau (QTP) has the largest extent of high altitude permafrost at the middle and low latitudes in northern hemisphere and is surrounded by dozens of seasonally frozen ground. Rising air temperatures have resulted in frozen ground degradation over QTP since the last century. Based on the daily frozen soil depth, annual mean daily minimum air temperatures and annual mean air temperatures obtained from 19 in-situ observations over QTP, the changes in the thickness, temporal and spatial distributions of frozen ground, as well as the associated attributions, are analyzed for the period of 1960-2019. The results show that the maximum depth of frost penetration, the beginning time of soil freezing and the ending time of soil thawing have changed considerably. On average, the maximum depth of frost penetration (MDFP) has reduced by 0.14~1.71 m at most stations. The annual frozen period has decreased by about 40 days. The changes in seasonal freezing of soils appear to be attributed to the rising of minimum air temperatures in winter, especially at the higher elevations range from 4500 to 5000 m.